2006
DOI: 10.2175/193864706783797366
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Anaerobic-Aerobic Digestion for Enhanced Volatile Solids Reduction and Nitrogen Removal

Abstract: Sequential anaerobic -aerobic digestion has been studied for use in wastewater treatment, but has had limited use for digestion of waste solids. Recent studies suggest that some solids in sludge are degraded only during anaerobic digestion and some only during aerobic digestion. Therefore, dual digestion (anaerobic/aerobic) would be expected to provide volatile solids reduction beyond that achieved by either anaerobic or aerobic digestion alone. In this investigation, dual digestion was compared to single stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Gas production, percentage gas distribution, pH, DO, digester temperature, chemical oxygen demand (COD), TKN, ammonia, selected dissolved ions and volatile fatty acids (VFA) were conducted and results are discussed elsewhere (Kumar et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Gas production, percentage gas distribution, pH, DO, digester temperature, chemical oxygen demand (COD), TKN, ammonia, selected dissolved ions and volatile fatty acids (VFA) were conducted and results are discussed elsewhere (Kumar et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…In the literature (Kumar et al, 2006a(Kumar et al, , 2006b low SRTs are suggested for the aerobic phase that can be considered to be a finishing step to complete the removal process initiated in the anaerobic one. Instead, if it is desired to reduce the nitrate load recycled to the WWTP with the supernatant from the digester, the optimal SRT should be high enough to ensure efficient nitrification and simultaneous denitrification.…”
Section: Nitrogen Removalmentioning
confidence: 99%
“…The basic motivation behind this approach arises from the different reaction environments (anaerobic and aerobic) provided to attain optimal biodegradability conditions for the different volatile solid (VS) sludge fractions. This point is well addressed in Kumar et al (2006aKumar et al ( , 2006b reporting a simple classification for the sludge constituent fractions in terms of VS degradability:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents an additional opportunity for water resource recovery facilities to reduce their ammonia discharge. Other advantages of sequential AN/AERO digestion are the improved digestate dewaterability (Kumar et al, 2006b), enhanced pathogen destruction and reduction in odorcausing volatile sulphur compounds (Banjade, 2008).…”
Section: Introductionmentioning
confidence: 99%